A Review of Transaction Management Algorithms in Distributed Databases - Effatparvar, Mehdi; Moradi, Amirhosein (Journal of Information Systems Research and Practice, 2024)
This paper provides a comprehensive review of transaction management algorithms in distributed databases, which are a critical part of modern IT infrastructure. The paper discusses traditional protocols such as Two-Phase Commit (2PC) and Three-Phase Commit (3PC), exploring their limitations in terms of scalability, fault tolerance, and concurrency control. Additionally, new decentralized approaches leveraging blockchain technology and smart contracts are examined, with a focus on how Proof of Work (PoW) and Proof of Stake (PoS) are utilized to enhance transaction transparency and security. Despite significant advancements, challenges remain, particularly in achieving strong concurrency control and ensuring fault tolerance among nodes. The paper concludes with a discussion of emerging trends and the potential of blockchain technology to address these issues, offering a transformative perspective on the management of distributed transactions.